Precision medicine in catecholaminergic polymorphic ventricular tachycardia: Recent advances toward personalized care - Anthony Siu; Edelyne Tandanu; Brian Ma; Evbayekha Endurance Osas; Haipeng Liu; Tong Liu; Oscar Hou In Chou; Helen Huang; Gary Tse (Wolters Kluwer Medknow Publications, 2023)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare inherited cardiac ion channelopathy where the initial disease presentation is during childhood or adolescent stages, leading to increased risks of sudden cardiac death. Despite advances in medical science and technology, several gaps remain in the understanding of the molecular mechanisms, risk prediction, and therapeutic management of patients with CPVT. Recent studies have identified and validated seven sets of genes responsible for various CPVT phenotypes, including RyR2, CASQ-2, TRDN, CALM1, 2, and 3, and TECRL, providing novel insights into the molecular mechanisms. However, more data on atypical CPVT genotypes are required to investigate the underlying mechanisms further. The complexities of the underlying genetics contribute to challenges in risk stratification as well as the uncertainty surrounding nongenetic modifiers. Therapeutically, although medical management involving beta-blockers and flecainide, or insertion of an implantable cardioverter defibrillator remains the mainstay of treatment, animal and stem cell studies on gene therapy for CPVT have shown promising results. However, its clinical applicability remains unclear. Current gene therapy studies have primarily focused on the RyR2 and CASQ-2 variants, which constitute 75% of all CPVT cases. Alternative approaches that target a broader population, such as CaMKII inhibition, could be more feasible for clinical implementation. Together, this review provides an update on recent research on CPVT, highlighting the need for further investigation of the molecular mechanisms, risk stratification, and therapeutic management of this potentially lethal condition.